Partial Substitution Of Wheat Flour With Locust (Locusta Migratoria) Powder In White Salted Noodle Incorporated With Spi And Mtg With Incomplete Information: An Experimental Study. - Zainal Abidin, Nur Amirah (Pusat Pengajian Teknologi Industri, 2021)
The increasing population is threatening the food security as the protein source from plants and animals is insufficient. Migratory locust is permissible in Islam and contain quite high protein content. SPI and MTG may help to strengthen the noodle structure. The aim of the research is to survey the possible formulation for white salted noodle made from locust powder by evaluating the cooking quality of white salted noodle as locust powder is partially substituted locust powder (5 and 10% by flour weight) and investigate the effect of SPI and MTG as food binder. The noodle maker kneaded the ingredients for 3 minutes and let it rest for 8 minutes.